Youth Civic Engagement, Knowledge and Literacy as Challenges to the Modern Democracy: A Participatory Approach to Civics Education as a Policy Response in Canada - Manley, Alec (Université d'Ottawa | University of Ottawa, 2012)
Across the Western world, many democracies are facing the same problem as Canada – youth civic engagement, knowledge and attentiveness to the political realm are in sharp decline. This reality creates a difficult situation for policy makers and politicians alike, as disengagement to this degree has never been experienced before. In Canada, youth voter turnout is at all time lows, with no signs of rebounding. More and more, young people today lack both the skills they need to engage with the political system and the interest to do so. There are some attempts being made across the country to help improve upon this through high school civics education, but they lack the appropriate pedagogy and sufficient support from politicians and governments at large. Though, in Ontario civics education does exist and through a discussion of the policy process and agenda setting, its presence will be considered in terms of how it passed through policy channels to become a part of the high school curriculum. Furthermore, research has shown that youth civic disengagement is a very real problem across Canada and led to some experts calling today’s youth political dropouts. Without action to bring more young people back from their apathetic stand, our democracy will face crucial challenges with regard to participation at the polls and maintaining an informed and active citizenry into the future. However, new approaches have been applied in other jurisdictions and have shown some success, offering frameworks for Canada to consider.